35‐1: Invited Paper: Carbon Nanotube Thin Film Transistors and Vertically Gated OLEDs. Issue 1 (May 2017) - Li, Huaping
Abstract : Electronically pure semiconducting single‐walled carbon nanotube ink is deposited to replace amorphous silicon layer in amorphous silicon thin film transistors manufacturing lines, giving rise to the transfer characteristics that have been applied in contemporary display backplanes. Vertically Gated OLEDs are achieved by tailoring the electron injection through external electric field.